TRENDS IN THE DEVELOPMENT AND IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES INTO THE ECONOMY (Web of Discoveries: Journal of Analysis and Inventions, 2023)
The definitions of the concept “artificial intelligence” are considered. The impact of artificial intelligence technologies on global economic growth, the labor market, and the financial sector is explored. Both positive aspects and threats caused by their introduction into the economy are analyzed.